Edukasi kesehatan untuk Meningkatkan Kenyamanan dan Mengurangi Resiko Kesehatan Selama Penerbangan - Sinta Fresia; Dwi Ambarwati; Nur Afni Wulandari (Jurnal Medika: Medika, 2026)
The number of Umrah pilgrims from Indonesia is increasing every year. Long-haul flights to Saudi Arabia with a duration of 9–12 hours can pose a risk of various health problems for Umrah pilgrims, such as Deep Vein Thrombosis (DVT), dehydration, Jet Lag, Respiratory Tract Infections (ARI), and fatigue. Lack of knowledge regarding preventive measures and healthy behaviors during long-haul flights on airplanes can increase health risks and disease complications. The results of the assessment of the level of knowledge before being given health education regarding aviation health were for 40 respondents in the Qathunnadaa Islamic study group Umrah pilgrims, obtained that the majority of respondents had a good level of knowledge, namely 17 people (42.5%). Respondents with a moderate level of knowledge numbered 15 people (37.5%), while respondents with a low level of knowledge numbered 8 people (20%). The method of community service activities starts from preparation, implementation of counseling with interactive lectures, demonstrations of stretching exercises during the plane, discussions, distribution of booklets and educational videos, mentoring and evaluation (pre-test-post-test) and reporting on program sustainability. After being given Health Education on the topic of aviation health, there was an increase in the level of knowledge to good for 30 people (75%) and a moderate level of knowledge for 10 people (25%). Thus, this community service program is expected to increase the congregation's understanding of the importance of maintaining health and minimizing health risks, especially during airplane flights.